2017
DOI: 10.1016/j.bbadis.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Modeling schizophrenia pathogenesis using patient-derived induced pluripotent stem cells (iPSCs)

Abstract: Schizophrenia is a chronic disabling mental disorder that affects about 1% population world-wide, for which there is a desperate need to develop more effective treatments. In this minireview, we summarize the findings from recent studies using induced pluripotent stem cells to model the developmental pathogenesis of schizophrenia and discuss what we have learned from these studies. We also discuss what are the important next steps and key issues to be addressed to move the field forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 77 publications
0
16
0
1
Order By: Relevance
“…Based on the high heritability of SCZ 11 , iPSC technology 12 can be used to generate disease-relevant developmental tissues and to study molecular and cellular abnormalities occurring during early development 1320 , on the condition that well-defined and homogeneous populations of disease-relevant cell types can be consistently generated from iPSCs. Many iPSC-derived neurons used in SCZ studies have been mixed populations of different neuronal subtypes 21 , often with varying proportions of subtypes from batch to batch. Such heterogeneity can address some issues but could also have resulted in variability of culture composition, leading to missed or false differences, and an inability to in identify abnormalities of specific processes in specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the high heritability of SCZ 11 , iPSC technology 12 can be used to generate disease-relevant developmental tissues and to study molecular and cellular abnormalities occurring during early development 1320 , on the condition that well-defined and homogeneous populations of disease-relevant cell types can be consistently generated from iPSCs. Many iPSC-derived neurons used in SCZ studies have been mixed populations of different neuronal subtypes 21 , often with varying proportions of subtypes from batch to batch. Such heterogeneity can address some issues but could also have resulted in variability of culture composition, leading to missed or false differences, and an inability to in identify abnormalities of specific processes in specific cell types.…”
Section: Introductionmentioning
confidence: 99%
“…These findings demonstrate the potential of homogeneous iPSC-derived neural subtypes for unraveling disease mechanisms. In this example, the mixed cell populations used in most previous iPSC disease modeling studies 10 would not have allowed detection of cell type-specific pathological changes of minor populations. We also obtained a homogeneous population of glutamatergic neurons using Ngn2-based induction, a well-accepted protocol in the field 39 , though there is a caveat that the induced glutamatergic neurons may not be identical to in vivo glutamatergic neurons.…”
Section: Discussionmentioning
confidence: 99%
“…SCZ modeling using iPSCs has begun 9 , and there has been a steady stream of studies reporting SCZ-specific transcriptome aberrations and cellular phenotypes in iPSC-derived neural tissues 10 . It will be important to sort out causal abnormalities vs. changes in effectors downstream of causal abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of reprogramming technology, research into neurological disorders 42 45 and neurodegenerative diseases 46 49 initially focused on establishing whether the reprogramming process was equally efficient in cells from healthy individuals and in cells from individuals with disease. The aim of this work was to ensure that hiPSCs would provide a valid system for modelling disease.…”
Section: Switching Gearsmentioning
confidence: 99%
“…The appropriate cohort size depends on the aims of the specific study and intervention; however, until 2015 hiPSC studies of familial and sporadic AD used four or fewer distinct hiPSC lines or clones 47 . Unfortunately, this limitation is not unique to research into idiopathic conditions such as AD but is also observed in hiPSC studies of genetic diseases (for example, HD 52 ) and complex psychiatric conditions (for example, schizophrenia 45 ), both of which are usually studied in clinical trials that include large cohorts of participants who are carefully stratified to maximize signal-to-noise ratio.…”
Section: Switching Gearsmentioning
confidence: 99%